Inactivation of Japanese encephalitis virus in plasma by methylene blue combined with visible light and in platelet concentrates by ultraviolet C light. Issue 11 (23rd August 2020) - Rustanti, Lina; Hobson‐Peters, Jody; Colmant, Agathe M. G.; Hall, Roy A.; Young, Paul R.; Reichenberg, Stefan; Tolksdorf, Frank; Sumian, Chryslain; Gravemann, Ute; Seltsam, Axel; Marks, Denese C.; Faddy, Helen M.
Background: Japanese encephalitis virus (JEV) is endemic to tropical areas in Asia and the Western Pacific. It can cause fatal encephalitis, although most infected individuals are asymptomatic. JEV is mainly transmitted to humans through the bite of an infected mosquito, but can also be transmitted through blood transfusion. To manage the potential risk of transfusion transmission, pathogen inactivation (PI) technologies, such as THERAFLEX MB‐Plasma and THERAFLEX UV‐Platelets systems, have been developed. We examined the efficacy of these two PI systems to inactivate JEV. Study Design and Methods: Japanese encephalitis virus–spiked plasma units were treated using the THERAFLEX MB‐Plasma system (visible light doses, 20, 40, 60, and 120 [standard] J/cm2) in the presence of methylene blue at approximately 0.8 μmol/L and spiked platelet concentrates (PCs) were treated using the THERAFLEX UV‐Platelets system (UVC doses, 0.05, 0.10, 0.15, and 0.20 [standard] J/cm2). Samples were taken before the first and after each illumination dose and tested for infectivity using an immunoplaque assay. Results: Treatment of plasma with the THERAFLEX MB‐Plasma system resulted in an average of 6.59 log reduction in JEV infectivity at one‐sixth of the standard visible light dose (20 J/cm2). For PCs, treatment with the THERAFLEX UV‐Platelet system resulted in an average of 7.02 log reduction in JEV infectivity at the standard UVC dose (0.20 J/cm2). Conclusions: The THERAFLEX MB‐Plasma and THERAFLEX UV‐Platelets systems effectively inactivated JEV in plasma or PCs, and thus these PI technologies could be an effective option to reduce the risk of JEV transfusion transmission.